Monetary policy - conventional and unconventional : taming the financial crisis - Hogan, John D. (Economics and Business Review, 2012)
Induced by the Great Recession of 2007-2009, and especially by the 2008 financial crisis, the Federal Reserve (Fed) undertook unconventional policies that probably saved the financial system from meltdown, but may have effected far-reaching consequences for years ahead. Quite apart from fulfilling its mandates to promote economic growth and maintain stable prices, the Fed made loans to specific financial institutions, accepted hitherto ineligible collateral, and purchased bonds that vastly enlarged its balance sheet and created unprecedented levels of excess bank reserves. How these events came to pass and their possible consequences - including potential inflation and loss of the Federal Reserve independence - are described in this article. (original abstract)